2020
DOI: 10.1111/jcmm.15668
|View full text |Cite
|
Sign up to set email alerts
|

Human amniotic mesenchymal stem cells inhibit hepatocellular carcinoma in tumour‐bearing mice

Abstract: Hepatocellular carcinoma (HCC) is the third leading cause of the cancer‐related death in the world. Human amniotic mesenchymal stem cells (hAMSCs) have been characterized with a pluripotency, low immunogenicity and no tumorigenicity. Especially, the immunosuppressive and anti‐inflammatory effects of hAMSCs make them suitable for treating HCC. Here, we reported that hAMSCs administrated by intravenous injection significantly inhibited HCC through suppressing cell proliferation and inducing cell apoptosis in tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…hADSCs are easily isolated and propagated ex vivo. hAMSCs show a fibroblast-like morphology in culture [ 24 , 25 ], while hAESCs exhibit a cobblestone-like morphology [ 23 ]. Compared with stem cells from other sources, hADSCs have the following advantages: (1) Easy to obtain, abundant sources, and no ethical and moral disputes: as the remaining after fetal birth the amniotic membrane can be used for separation of hAMSCs and hAESCs, which will not harm the donors; (2) No tumorigenicity: numerous studies showed that hADSCs had no proliferation and growth on soft agar in vitro, no colonies formed, no teratoma formation after implanting NOD-SCID mice in vivo [ 24 ]; (3) Low immunogenicity and high histocompatibility: hADSCs were considered as the immune-privileged cells and showed remarkable characteristics of low immunogenicity [ 26 , 27 ].…”
Section: Characteristics Of Human Amnion-derived Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…hADSCs are easily isolated and propagated ex vivo. hAMSCs show a fibroblast-like morphology in culture [ 24 , 25 ], while hAESCs exhibit a cobblestone-like morphology [ 23 ]. Compared with stem cells from other sources, hADSCs have the following advantages: (1) Easy to obtain, abundant sources, and no ethical and moral disputes: as the remaining after fetal birth the amniotic membrane can be used for separation of hAMSCs and hAESCs, which will not harm the donors; (2) No tumorigenicity: numerous studies showed that hADSCs had no proliferation and growth on soft agar in vitro, no colonies formed, no teratoma formation after implanting NOD-SCID mice in vivo [ 24 ]; (3) Low immunogenicity and high histocompatibility: hADSCs were considered as the immune-privileged cells and showed remarkable characteristics of low immunogenicity [ 26 , 27 ].…”
Section: Characteristics Of Human Amnion-derived Stem Cellsmentioning
confidence: 99%
“…It has been reported that hAMSCs were able to home to tumor sites and inhibit the growth of human hepatoma cells by promoting cell apoptosis and inhibiting cell proliferation [ 159 ]. We demonstrated that the mechanisms of hAMSCs’ anti-hepatocellular carcinoma were mainly involved in their paracrine effects, in which hAMSC-derived DKK-3, DKK-1 and IGFBP-3 markedly inhibited cell proliferation and promoted apoptosis of Hepg2 cells through suppressing the Wnt/β-catenin signaling pathway and IGF-1R-mediated PI3K/AKT signaling pathway, respectively [ 25 ]. hAMSCs also significantly reduce the proliferation of cancer cell lines of hematopoietic [ 160 ] and prostate cancer [ 161 ] by inducing cell cycle arrest and inducing C6 glioma apoptosis through the Bcl-2/Caspase pathways [ 162 ].…”
Section: Cell-based Therapy With Human Amnion-derived Stem Cellsmentioning
confidence: 99%
“…Dickkopf-related protein 3 (DKK-3) is a secreted glycoprotein with a molecular weight of 38 kDa that is synthesized by stressed tubular epithelia and is significantly expressed in mesenchymal progenitor and mesenchymal cells in vitro (Meister et al, 2015;Federico et al, 2016). DKK3 is a multifunctional protein involved in various cellular processes, such as cell differentiation, proliferation and apoptosis, via the Wnt/β-catenin pathway (Veeck and Dahl, 2012) and contributes to multiple diseases, including cancer (Liu et al, 2020b), chronic heart failure (Cao et al, 2018), and acute myeloid leukemia (Xu et al, 2017). The Wnt/β-catenin pathway is one of the important signaling pathways leading to kidney disease (Ke et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Studies demonstrated that hAMSCs have a great potential for stem cell-based therapy in many diseases due to their pluripotency, low immunogenicity, no tumorigenicity, potent paracrine effects, and no ethical concern [ 23 ]. We previously observed that both hAMSCs and their CM efficiently repaired skin injury [ 24 ], inhibited hepatocellular carcinoma [ 25 ], and alleviated HFD-induced hyperglycemia in mice (unpublished data), suggesting that hAMSCs-CM plays a key role in the cells-based therapy by their paracrine effects through afftecting immunoregulation and anti-inflammation. It has been reported that exosomes from adipose MSCs ameliorated HFD-induced obesity in mice through anti-inflammation, improving insulin sensitivity and decreasing hepatic steatosis [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Human amniotic mesenchymal stem cells (hAMSCs) are considered as a promising source of stem cells for cell-based therapy due to their characteristics such as pluripotency, low immunogenicity, no tumorigenicity, potent paracrine effects, and no ethical concern [ 23 ]. Previously, we observed that both hAMSCs and their CM efficiently repaired skin injury [ 24 ], inhibited hepatocellular carcinoma [ 25 ], and alleviated HFD-induced hyperglycemia in mice (unpublished data). It has been reported that adipose MSC-derived exosomes ameliorated HFD-induced obesity in mice through inhibiting inflammation, improving insulin sensitivity, and decreasing hepatic steatosis [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 97%